PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI YAYASAN DOMPET DHUAFA JAKARTA. - A Rafiq (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
This study aims to analyze the Effect of Organizational Culture and Work Motivation on the Employee Performance of the Dompet Dhuafa Republika Foundation in Jakarta. The method used is Multiple Linear Regression analysis where it is assumed that the variable Organizational Culture and Work Motivation has an influence on the Employee Performance of the Dompet Dhuafa Republika Foundation in Jakarta. The results obtained state that Organizational Culture and Work Motivation have an influence on employee performance by 54.2%. Organizational Culture Variables have a dominant influence on employee performance. From the results of the study, it is expected that in the future, the application of organizational culture will be further enhanced so that it is truly pervasive and imbued by every individual in the dhuafa wallet. In addition, it is necessary to develop employees in the form of rewards and clear rewards, both in the form of material rewards and career advancements and increasing knowledge in accordance with employee achievements to generate high motivation from their employees.Keywords: Organizational Culture, Work Motivation, Employee Performance.